Exploitation and Governance in Pakistan: Institutional Failures and Reform Pathways - Ahmad Saeed Chishti; Muhammad Ali Raza; Usman Anwar, (Dialogue Social Science Review (DSSR), 2025)
The persistent challenges of governance in Pakistan through the lens of institutional failure and systemic exploitation. It explores how weak institutional frameworks, politicization of public offices, and lack of accountability have entrenched corruption and hindered democratic development. Drawing on case studies and historical analysis, the paper identifies key areas where exploitation both economic and political has thrived under ineffective governance structures. Special attention is given to how marginalized communities withstands the worst of these failures. The study also outlines viable reform pathways, emphasizing institutional restructuring, judicial independence, bureaucratic transparency, and civic engagement. Through the proposing evidence-based solutions, the paper aims to contribute to the discourse on sustainable governance reform in Pakistan. Keywords: Institutional Failure, Governance Reform, Political Exploitation, Corruption in Pakistan, Accountability Mechanisms